PENGARUH MOOD, PEMBERIAN REWARD DAN KOMITMEN RELIGIUS TERHADAP NIAT MELAKUKAN WHISTLEBLOWING - Ester Sabatini (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
Many countries, including Indonesia, face serious socio-economic problems due to fraud in various forms, including corruption. Whistleblowing is one way to restore public trust, especially in terms of preventing fraud. This research aims to explore how big the relationship between mood, the influence of rewards, and a person's religious commitment has on the desire or intention to carry out whistleblowing. In this quantitative research, primary data was collected through a questionnaire distributed using Google Form. The purposive sampling method was used to select 70 respondents. Analysis was carried out using the multiple linear regression method. Research findings show that mood, giving rewards, and religious commitment each have an influence on a person's desire to carry out whistleblowing.